2017
DOI: 10.2174/0929867324666170823125330
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic Connection between Dietary Phytochemicals and ATP Synthase

Abstract: For centuries, phytochemicals have been used to prevent and cure multiple health ailments. Phytochemicals have been reported to have antioxidant, antidiabetic, antitussive, antiparasitic, anticancer, and antimicrobial properties. Generally, the therapeutic use of phy-tochemicals is based on tradition or word of mouth with few evidence-based studies. Moreo-ver, molecular level interactions or molecular targets for the majority of phytochemicals are unknown. In recent years, antibiotic resistance by microbes has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 141 publications
1
30
0
1
Order By: Relevance
“…From the microbiological perspective, the antimicrobial substances contained in acid whey and lemon juice, such as organic acids, whey protein, bacteriocins and polyphenols, were responsible for the inhibition of microbial growth. The pH reduction caused by organic acids (citric, lactic) was the primary factor that affected the reduction of microorganisms (Ahmad et al, 2017;Alvadaro and Mc Kee 2007;Amini et al, 2017). In the present study it was shown that after thermal treatment no aerobic bacteria were found in both the control group and in WM and LJM.…”
Section: Resultssupporting
confidence: 45%
“…From the microbiological perspective, the antimicrobial substances contained in acid whey and lemon juice, such as organic acids, whey protein, bacteriocins and polyphenols, were responsible for the inhibition of microbial growth. The pH reduction caused by organic acids (citric, lactic) was the primary factor that affected the reduction of microorganisms (Ahmad et al, 2017;Alvadaro and Mc Kee 2007;Amini et al, 2017). In the present study it was shown that after thermal treatment no aerobic bacteria were found in both the control group and in WM and LJM.…”
Section: Resultssupporting
confidence: 45%
“…According to the results of this and previous works [7,8], we can state that sulfonamide compounds, known as carbonic anhydrase inhibitors, are able to modify the activity of the chloroplast ATPase, a multisubunits enzyme, which has several active and regulatory centers [10], and can be a useful tool when studying the features of the catalytic process in membrane ATP synthases of various origins. The data of this and previous works [7,8] show for the first time that some compounds of the sulfonamide class are agents aimed at ATP synthase, which cause growing interest during the development of new methods of treating human and animal diseases and agricultural applications [27,28]. Вивчалася дія двох водорозчинних сульфаніламідів ароматичного 4амінобензолсульфоніламіду (СА) і аліфатичного трифторметилсульфоніламіду (ТФМСА) на латентну і стимульовану АТРазну активність каталітичної частини тилакоїдної АТРсинтази, ізольованої з хлоропластів шпинату.…”
Section: Fig 3 the Effect Of Carbonic Anhydrase Inhibitors On The Mmentioning
confidence: 87%
“…The 6-helices or a 5-helices structure is used as a receptor for protein or peptide docking [39]. Scientists are also looking at molecules that could block furin, which could be investigated as possible therapies [41,[49][50][51].…”
Section: Potential Of Spike Protein In Drug Discoverymentioning
confidence: 99%